Dose-dependent inhibition of human platelet aggregation by prasugrel and its interaction with aspirin in healthy subjects - Jakubowski, Joseph A; Payne, Christopher D; Weerakkody, Govinda J; Brandt, John T; Farid, Nagy A; Li, Ying G; Naganuma, Hideo; Lachno, D Richard; Winters, Kenneth J (Journal of cardiovascular pharmacology, 2007)
The aims of this open-label, randomized, dose-escalation pharmacodynamic study of prasugrel, an orally active antiplatelet agent, were to assess its interaction with aspirin (ASA, 325 mg) in healthy subjects after a loading dose (LD) and subsequent 5 days of once-daily maintenance doses (MD) of prasugrel or the active comparator, clopidogrel. We measured platelet aggregation induced by ADP, collagen, and TRAP and compared effects on maximal and residual platelet aggregation responses. On a background of ASA, subjects were randomly assigned to 1 of 4 prasugrel treatment groups (LD/MD in mg: 20/5, 30/7.5, 40/10, or 60/15; n = 8/group) or to clopidogrel 300 mg LD/75 mg MD (n = 11). Prasugrel dose-dependently inhibited ADP-induced platelet aggregation and exhibited higher levels of platelet inhibition than clopidogrel or ASA alone. Prasugrel plus ASA resulted in additive inhibition of collagen- and TRAP-induced platelet aggregation. Although inhibition of residual aggregation was greater than inhibition of maximal aggregation, values were highly correlated. The safety and tolerability of prasugrel plus ASA were also monitored. Within the limitations of the study, prasugrel was found to be well tolerated when dosed as LD followed by MD in the presence of ASA and provided greater platelet inhibition than ASA alone.